Prognostic factors for patients undergoing vitrified-warmed human embryo transfer cycles: a retrospective cohort study. (3rd April 2017) - Takahashi, Toshifumi; Hasegawa, Ayumi; Igarashi, Hideki; Amita, Mitsuyoshi; Matsukawa, Jun; Takehara, Isao; Suzuki, Satoko; Nagase, Satoru
Abstract: We examined the prognostic factors for pregnancy in 210 vitrified-warmed embryo transfer (ET) cycles in 121 patients. The univariate analysis showed that age, gravida, the number of cycles associated with infertility caused by endometriosis, the number of previous assisted reproductive technology (ART) treatment cycles, and the number of ICSI procedures were significantly lower in pregnant cycles compared with non-pregnant cycles. The percentages of ET using at least one intact embryo and of ET using at least one embryo that had developed further after warming were significantly higher in pregnant cycles compared with non-pregnant cycles. Multivariate logistic regression analysis showed that previous ART treatment cycles, ET with at least one intact embryo, and ET using at least one embryo that had developed further were independent prognostic factors for pregnancy in vitrified-warmed ET cycles. We conclude that fewer previous ART treatment cycles, ET using at least one intact embryo, and ET with embryos that have developed further after warming might be favourable prognostic factors for pregnancy in vitrified-warmed ET cycles.